2020
DOI: 10.1017/ehs.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Munda languages are father tongues, but Japanese and Korean are not

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…An alternative linguistics theory for the origins of agriculture in Yunnan, instead, links the dispersal of rice out of this region, including into China. Van Driem (2012 has suggested that domesticators of rice could have involved Austroasiatic and early Tibeto-Burman speakers and ancestors to Austronesian all spreading from the eastern Himalayan region, from around the region of northeast India and Myanmar, with certain O-haplogroups of the Y-chromosome (Chaubey and van Driem 2020). As already noted above, this is at odds with archaeological evidence for rice domestication, but it raises the importance of improving the empirical evidence for past crops and plant use in Yunnan.…”
Section: Previous Theories On the Origins Of Agriculture In Yunnanmentioning
confidence: 99%
“…An alternative linguistics theory for the origins of agriculture in Yunnan, instead, links the dispersal of rice out of this region, including into China. Van Driem (2012 has suggested that domesticators of rice could have involved Austroasiatic and early Tibeto-Burman speakers and ancestors to Austronesian all spreading from the eastern Himalayan region, from around the region of northeast India and Myanmar, with certain O-haplogroups of the Y-chromosome (Chaubey and van Driem 2020). As already noted above, this is at odds with archaeological evidence for rice domestication, but it raises the importance of improving the empirical evidence for past crops and plant use in Yunnan.…”
Section: Previous Theories On the Origins Of Agriculture In Yunnanmentioning
confidence: 99%
“…In contrast, the label ‘Japonic’ is restricted to the insular variety, the language family composed of Mainland Japanese and the Ryukyuan languages. Several articles in this special edition, such as those by Mark Hudson et al ( 2020 ), Elisabeth de Boer et al ( 2020 ) and Gyaneshwer Chaubey & George van Driem ( 2020 ), deal with the advent and spread of Proto-Japonic. Although the authors disagree on the exact timing, they all agree that Japonic entered the Japanese islands via the southern tip of the Korean peninsula, with the ancestral speakers settling in northern Kyushu and eventually spreading to the rest of the Japanese islands.…”
Section: The Transeurasian Languagesmentioning
confidence: 99%
“…They argue that there is a limited core of similarities for which the most sensible linguistic explanation is inheritance. Although most contributions in our special edition take a neutral attitude with regard to the deeper affinity of the Transeurasian languages, four contributions, notably those by Cui et al (2020), Nelson and colleagues (2020), Wang and Robbeets (2020) and Chaubey and van Driem (2020), accept the affiliation hypothesis as a point of departure for their research.…”
mentioning
confidence: 99%
“…While various models for the origins of Japanese populations have been previously proposed based on genetic, archaeological and linguistic evidence, including alternative versions of a tripartite structure (Chaubey & van Driem, 2020; van Driem, 2021), the ‘dual structure’ hypothesis, originally formulated based on craniofacial data (Hanihara, 1991), is the most widely known and enduring (Hudson et al, 2020). In this model, all Japanese populations are the descendants of the gradual mixing of two major sources of ancestry: the initial Jomon and subsequent Northeast Asian migrants during the Yayoi period.…”
Section: Introductionmentioning
confidence: 99%